The Effect of Company Financial Systems and Construction Management on the Implementation of Quality Management Systems and Production Quality in Construction Companies (Financial Management Literature Review) - Gatot Subiarto (Dinasti International Journal of Management Science, 2022)
Article Literature Review of the Influence of the Company's Financial System, and Construction Management on the Implementation of Quality Management Systems and Production Quality in Construction Companies is a scientific article that aims to build a research hypothesis on the influence of inter-variables to be used in further research, within the scope of the science of Financial Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) The Company's Financial System influences the Implementation of Quality Management Systems; 2) Construction Management has an effect on the Implementation of the Quality Management System; 3) The Company's Financial System affects the Quality of Production in Construction Companies; 4) Construction Management affects Production Quality in Construction Companies; and 5) Implementation of the Quality Management System affects Production Quality in Construction Companies. In addition to these 2 exogenous variables that affect endogenous variables.